Peran Lembaga Pengembangan Tilawatil Qur;an Kecamatan Bandar Masilam dalam Membentuk Peserta Musabaqah Tilawatil Qur'an - Syahid, Ibnu (TSAQOFAH, 2023)
LPTQ is an institution or forum that functions to broadcast the Koran in people's lives. One of the programs implemented by LPTQ is Musababaqah Tilawatil Quran or commonly known as MTQ. With the implementation of MTQ, it can arouse the enthusiasm of the community and young people in Bandar Masilam District in reading, understanding and practicing the Koran in everyday life. So as to make the community and younger generations who are Quranic, so that quality Musabaqah participants are formed. This research aims to find out how the role of LPTQ and the constraints experienced by LPTQ in carrying out its programs. This study used field research methods, in which the writer went directly to the field to find the necessary data according to the problem under study, processed through the process of data collection, data classification and data interpretation using observation, interview and documentation techniques. The results of this study indicate that the Bandar Masilam District LPTQ has a very large influence on people's lives. LPTQ Bandar Masilam Subdistrict makes every effort to carry out its duties. LPTQ collaborates with Koran teachers, Koran agencies, schools, and the local government to make it easier for them to carry out their duties. However, LPTQ Bandar Masilam Subdistrict cannot be said to be growing rapidly, however LPTQ Bandar Masilam Subdistrict has experienced good changes every year as seen from the several achievements of the participants of the musabaqah which have increased. The obstacles experienced were funding constraints and human resource constraints.